Environmental and Social Management Plan (ESMP) for Pilot of Climate Smart Agricultural Innovations and Climate Information Service Technologies in Zambia - International Water Management Institute; WorldFish; International Institute of Tropical Agriculture (2024)
In light of the potential E&S risks envisaged on these demonstration activities, the AICCRA E&S team conducted a detailed, site-specific E&S risk assessment of selected locations for the CSA demonstration in Luapula and Central Provinces October and November 2024. These assessments confirmed that, without effective mitigation measures, the identified E&S risks could adversely impact people and the environment. To address these findings, the AICCRA Zambia team has developed this Environmental and Social Management Plan (ESMP) to outline strategies for addressing the identified E&S risks at the demonstration sites. This ESMP, prepared in collaboration with key project stakeholders, will be disclosed before initiating project activities and updated as necessary when new risks or CSA sites are identified.